Nursing women's mental health in the perinatal period (Research, Society and Development, 2025)
Introduction: The perinatal period is a cycle of biopsychosocial changes for women. This research addresses women's mental health during pregnancy and the postpartum period, stages marked by intense changes. Objective: The study aims to identify the prevalence of mental disorders that affect women during these periods, and to investigate factors that influence mental health, such as the prevalence of depression, anxiety disorders, and eating disorders, in addition to highlighting the role of nursing in preventing these disorders. Methodology: This is an integrative literature review, based on the analysis of 5 scientific articles published between 2015 and 2025 found in the Virtual Health Library (VHL). Data collection was performed in indexed databases, with strict inclusion and exclusion criteria. Results: The results highlight the need for specialized attention in primary health care, reinforcement in the training of nursing professionals, and greater focus on public policies that promote maternal well-being. Conclusion: The study contributes to the expansion of knowledge in the area of ​​women's health, with practical implications for holistic care for pregnant and postpartum women.